Demografi Obesitas Sentral di Indonesia (Analisis SKI 2023) - Indriasih Olyn Simanungkalit; Bona Simanungkalit (Prodi Kebidanan Blora Program Diploma Tiga Poltekkes Kemenkes Semarang, 2026)
The 2023 Indonesian Health Survey (SKI) report shows that the prevalence of central obesity in the population aged 15 years and over has reached 36.8%. The purpose of this study was to identify the prevalence of central obesity by age group, education level, and employment status. Furthermore, it was also to determine the relationship between age, education level, and employment status with abdominal circumference (central obesity). This study was a quantitative study with a secondary data analysis design from the 2023 Indonesian Health Survey (SKI). The study sample consisted of men with complete data on anthropometric measurements (abdominal circumference) and demographic characteristics. The sampling technique used was multistage random sampling. Analysis using the chi-square test was conducted to examine the relationship between age, education level, and employment status with central obesity (abdominal circumference measurement). The results showed a significant relationship between age, education level, and employment status with central obesity (abdominal circumference measurement), with each p-value <0.001. It is recommended that a health stewardship approach should focus on lifestyle interventions in the workplace and health education for productive age groups to prevent a heavier burden of heart disease in the future.